Lifestyle Change Intervention with Modified Salt Substitution for Hypertension Patients: A Quasi-Experimental Study - Rahayu, Trio Gustin; Ernawati, Ernawati; Riyanto, Dwi Agung (Chakra Brahmanda Lentera Institute, 2025)
Background: Hypertension is a major global health problem. Lifestyle changes, including reducing sodium intake, are important strategies for managing hypertension. This study aims to evaluate the effectiveness of an integrated lifestyle intervention focusing on the use of salt substitutes in controlling blood pressure in patients with hypertension. Methods: A quasi-experimental study design was used, involving 15 respondents. The study was conducted at the Singandaru Health Centre in Serang City, Banten. Participants were required to be over 40 years old, have a systolic blood pressure of over 40 years old, have a systolic blood pressure of over 140 mmHg and a diastolic blood pressure of over 90 mmHg, and have a history of hypertension. The respondent's blood pressure was measured before and after they underwent a 7-day course of modified low-sodium salt therapy. Analysis in the study using the t-test with a normality test first. Results: The respondents with high blood pressure, 60% were male, with an average age of 62 years. In terms of education, most respondents had attended junior high school or high school. Before the salt substitute modification intervention, the average blood pressure of respondents was categorized as grade 2 hypertension. After the intervention, it was classified as grade 1 hypertension. There was an effect of low sodium salt consumption on systolic (p<0.001) and diastolic blood pressure (p=0.045). Conclusion: Being disciplined in food choices and using low-sodium salt can significantly contribute to pressure reduction. Health professionals can provide structured education and counselling on low salt diets, appropriate use of salt substitutes, importance of physical activity, stress management, and other aspects of lifestyle change.